2002
DOI: 10.1097/00003246-200203000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Sedation modulates recognition of novel stimuli and adaptation to regular stimuli in critically ill adults

Abstract: Commonly administered sedative medications may alter the brain's biophysical state and thereby modulate specific aspects of the brain's information processing and adaptive functions. These functions can be interrogated even when the patient is seemingly unresponsive. If this observation is confirmed in subsequent prospective controlled randomized trials, electrophysiologic interrogation of the brain's information processing and adaptive capacities could serve as an adjunct to clinical assessment of responsiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…However, some degree of residual sedative effect due to potentially impaired metabolism might have influenced our findings. Clifford and Buchman [18] reported that the combination of benzodiazepine and fentanyl affected information processing in response to novel and standard stimuli in a different manner than the combination of propofol and fentanyl in intensive care patients. Nevertheless, both of these drug combinations globally reduced the amplitudes of the responses to all stimuli as the sedative drug dose increased, in a manner similar to that in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, some degree of residual sedative effect due to potentially impaired metabolism might have influenced our findings. Clifford and Buchman [18] reported that the combination of benzodiazepine and fentanyl affected information processing in response to novel and standard stimuli in a different manner than the combination of propofol and fentanyl in intensive care patients. Nevertheless, both of these drug combinations globally reduced the amplitudes of the responses to all stimuli as the sedative drug dose increased, in a manner similar to that in our study.…”
Section: Discussionmentioning
confidence: 99%
“…During mechanical ventilation, sedation has become an important component of the treatment, and intubated patients are frequently treated with sedatives (Young et al, 2000;Hurford, 2002;Izurieta and Rabatin, 2002). However, knowledge about the impact of pharmacological sedation on severely ill patients' memory and perception of discomfort is sparse (Wagner et al, 1997;Jones et al, 2000a;Capuzzo et al, 2001;Clifford and Buchman, 2002;Rundshagen et al, 2002), and no studies have focused on the relationship between mechanically ventilated patients' stressful experiences and the use of sedatives, including the depth of sedation.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are numerous reasons for disturbed memory and amnesia in critically ill patients [15,16,17], the amnestic properties of SAAs make the impact on memory evident [18]. A dose-dependent responsiveness has been suggested between commonly administered sedatives in the ICU and the formation and retention of memory [19,20]. Recent studies focusing on the relationship between SAAs and memory of the ICU have included measures of days and amount of sedation [21,22].…”
Section: Introductionmentioning
confidence: 99%